2015
DOI: 10.1186/s12983-015-0130-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for sex-specific plasticity in adult brain

Abstract: BackgroundPlasticity in brain size and the size of different brain regions during early ontogeny is known from many vertebrate taxa, but less is known about plasticity in the brains of adults. In contrast to mammals and birds, most parts of a fish’s brain continue to undergo neurogenesis throughout adulthood, making lifelong plasticity in brain size possible. We tested whether maturing adult three-spined sticklebacks (Gasterosteus aculeatus) reared in a stimulus-poor environment exhibited brain plasticity in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 51 publications
4
45
3
Order By: Relevance
“…The same applied to body size, body mass, and condition of the fish, indicating a lack of positive effect on growth and energy balance of the individuals. Although similar outcomes have been recorded in some earlier studies (reviewed in Näslund & Johnsson, 2016), our findings are noteworthy in light of the results from an earlier study conducted on this species, which found evidence for a positive effect of enrichment on male brain size (Herczeg et al., 2015). In contrast, we found that the degree of sexual size dimorphism (SSD) in brain was similar in both treatments and all populations included in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The same applied to body size, body mass, and condition of the fish, indicating a lack of positive effect on growth and energy balance of the individuals. Although similar outcomes have been recorded in some earlier studies (reviewed in Näslund & Johnsson, 2016), our findings are noteworthy in light of the results from an earlier study conducted on this species, which found evidence for a positive effect of enrichment on male brain size (Herczeg et al., 2015). In contrast, we found that the degree of sexual size dimorphism (SSD) in brain was similar in both treatments and all populations included in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we conducted a common garden experiment in which fish from four different populations were exposed to either a control (bare aquaria) or enriched (spatial complexity generated with physical structures) treatment over a period of 2 months. Based on the results of an earlier experiment which found that males developed larger brains in enriched tanks as compared to females (Herczeg et al., 2015), we expected to see a similar sex‐specific response to environmental enrichment consistent across the four populations tested. Apart from assessing the treatment effects on brain size and size of different brain parts, we also investigated how enrichment influenced growth (i.e., body size) and condition (i.e., residual mass) of the fish.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations